Flow Injection Electrochemical Quartz Crystal Microbalance with ICP-OES Detection: Electroprecipitation and Stripping of Lanthanum and Neodymium in a Flow Cell. Issue 3 (1st March 2023) - Molina, Daniel E.; Wall, Nathalie A.; Beyenal, Haluk; Ivory, Cornelius F.
Abstract : We used an improved version of our hyphenated analysis technique, flow injection electrochemical quartz crystal microbalance with inductively coupled optical emission spectroscopy (FI-EQCM-ICP-OES), to investigate the electroprecipitation of lanthanum and neodymium from flowing solutions. The improved version has two independent flow injection circuits, allowing different conditions for electrochemical precipitation (pH = 4.3 or 2.6) and quick stripping (2% HNO3 ) with EQCM mass detection and ICP-OES elemental analysis. Lanthanum or neodymium ions in a 500 μ l sample were injected into a carrier stream and deposited onto an electrochemical quartz crystal microbalance (EQCM) housed in a micro flow cell, owing to a localized high-pH layer. The deposits are subsequently stripped from the electrode using HNO3 and analyzed downstream using an ICP-OES. We found that using acidic solutions without supporting electrolyte leads to an increase of the amount of lanthanum detected by 4-fold. The enhanced deposition can be attributed to enhanced mass transfer by migration. Moreover, we showed that by applying chronopotentiometry, we can detect a change in the hydrogen evolution reaction mechanism that enables the precipitation of lanthanides on the surface of the electrode. Understanding and enhancing the deposition of lanthanides is relevant for elemental or isotopic detection in nuclear forensics.